ANALISIS KEGIATAN SENI RUPA DI SEKOLAH DASAR TERHADAP KREATIVITAS ANAK MELALUI MENGGAMBAR DAN MEWARNAI - Wijayanto, Wasis; Putri, Arinda Elfana; Yustantifa, Annabella (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2025)
This research aims to analyze the influence of fine arts activities on children's creativity in class 2 of SDN 1 Kramat, especially through drawing and coloring activities. The method used is qualitative with a descriptive approach. Data was collected through observation, interviews and documentation. The research results show that fine arts activities, such as drawing and coloring, can increase children's creativity in various aspects, including the ability to think imaginatively, problem solving and self-expression. Supporting factors include a supportive learning environment, availability of art tools, and an interactive learning approach. This research concludes that fine arts activities make a positive contribution to the development of children's creativity at the elementary school level.